DIGESTIBILIDADE APARENTE DO FARELO DE COCO E RESÍDUO DE GOIABA PELA TILÁPIA DO NILO (Oreochromis niloticus) - Elton Lima Santos; Maria do Carmo Mohaupt Ludke; José Milton Barbosa; Carlos Boa-Viagem Rabello; Jorge Vitor Ludke (Revista Caatinga, 2009)
This work it objectified determination apparent digestibility of Dry Matter (DM), of Fraction Crude Protein (CP), of Gross Energy (GE) and the Digestible Energy (DEa) and Digestible Protein (DPa) of the waste guava meal and coconut meal. 75 figerlings of Nile tilapia had used been (with initial weight of 20,00 ± 5,0g), kept per 25 days in glass aquariums (70 L of water, each one), were fed to satiation, in small fractions to each 2 hours, of the 8:00 to 17:00h, with three diets (three repetitions each one) contend 0,10% of oxide chromic (marked intern): a) the reference (half-purified); b) 30 % coconut meal and c) 30% of waste guava meal. The feces had been by "sifonagem" two times for day (in beginning of the morning and afternoon end). The values of digestibility of waste guava meal had been: DM 43,36%; CP 61,49%, GE 64,24%; DEa 3601,03 kcal/kg e DPa 6,89% and for coconut meal: MD 60,36%; CP 75,62%, GE 37,10%; DEa 1878,74 kcal/kg e DPa 15,60%. The tested ingredients present potential to be used in rations for figerlings of Nile tilapia.